A flexible computer-to-computer protocol for DISNET: a Distributed Instrument System NETwork - Gemperline, Paul J.; Megargle, Robert (East Carolina University, 1984)
This article evaluates the performance of a DISNET channel control module.
Keywords: DISNET; Distributed instrument system NETwork; Computer protocols; Network protocols; Channel control modules